2019
DOI: 10.4081/jlimnol.2019.1848
|View full text |Cite
|
Sign up to set email alerts
|

Life history of Karualona muelleri (Richard, 1897) (Chydoridae, Aloninae)

Abstract: Many taxonomic issues still need to be solved for the family Chydoridae, but mainly in the subfamily Aloninae. The species Karualona muelleri is an example of a recent taxonomic redefinition, since it was decoupled from the genus Alona and translocated to another genus. In order to expand our knowledge on the species, we investigated population growth and compared the morphometry of the first and second instars, male, parthenogenetic female, ephippial female, and ephippium. An experimental population was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similarly, CKD was a significant risk factor for in-hospital mortality (OR 2.14) in the univariable analysis of 200 COVID-19 positive patients admitted to a tertiary New York medical center; however, this association was not significant in the multivariable analysis 3 . CKD was also a significant risk factor for pneumonia (OR 2.05) and mortality (OR 2.48) among 23,162 positive patients from Mexico after adjusting for age, gender, and smoking status 4 . In addition, CKD was an independent significant risk factor for hospital visits but not for respiratory support requirements among the people who tested positive for COVID-19, according to an analysis of over 2 million COVID-19 smart app users 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, CKD was a significant risk factor for in-hospital mortality (OR 2.14) in the univariable analysis of 200 COVID-19 positive patients admitted to a tertiary New York medical center; however, this association was not significant in the multivariable analysis 3 . CKD was also a significant risk factor for pneumonia (OR 2.05) and mortality (OR 2.48) among 23,162 positive patients from Mexico after adjusting for age, gender, and smoking status 4 . In addition, CKD was an independent significant risk factor for hospital visits but not for respiratory support requirements among the people who tested positive for COVID-19, according to an analysis of over 2 million COVID-19 smart app users 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the intrinsic rates of population increase are affected by temperature, for instance, Hann (1985) found that increasing temperatures promoted higher reproductive rates in chydorids by decreasing egg maturation times; therefore, in four species the highest "r" values were recorded at 24 -25ºC. Despite A. guttata presented high growth rates in comparison to Pleuroxus aduncus (Jurine, 1820) 0.15/d (Nandini & Sarma, 2000), or very similar to those of C. rectangula or Karualona muelleri (Richard, 1897) (Muro-Cruz et al, 2002;Panarelli et al, 2019), such values are below the intrinsic growth rates that other cladocerans like Moina sp. can reach (Sipaúba-Tavares & Bachion, 2002;Deng & Xie, 2003;Rodríguez-Estrada et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Resting egg identification is a difficult task, because important taxonomic characteristics (head pores, postabdomen, antennae, antennula and trunk limbs) are not present in resting eggs. Even valve characteristics as marginal setae and denticles can be lost during the permanence in the sediment (Panarelli et al, 2019). Guerrero-Jiménez et al (2020) found no clear evidence of species-specificity between cladoceran resting eggs even with the use of Scanning Electron Microscope.…”
Section: Unique -Temporary Wetlandsmentioning
confidence: 94%